Larval tapeworms (Cestoda: Trypanorhyncha) from some Red Sea fishes, Yemen - Al-Zubaidy, A.B.; Mhaisen, F.T. (Mesopotamian Journal of Marine Sciences, 2022)
A total of 713 fish specimens belonging to 26 species and nine families from the Red Sea, Yemeni coastal waters were examined for the infection with trypanorhynchid cestodes during the period from September 2008 till February 2010. The results showed the occurrence of five different trypanorhynchids in viscera, body cavity and flesh of 12 fish species. These cestodes were: Pseudotobothrium dipsacum, Callitetrarhynchus gracilis, Floriceps minacanthus, Pseudogrillotia sp. and Nybelinia bisulcata. The first three species are recorded here for the first time in fishes from Yemeni waters of the Red Sea. Also, two fish species (Lethrinus mahsena and Valamugil seheli) are considered as new hosts for N. bisulcata in the Yemeni waters of the Red Sea. C. gracilis was found in nine different fish species. Five fish species (Pomodasys argenteus, Lethrinus lentjan, L. nebulosus, Scomberomorus commerson and Thunnus tonggol) harbored three trypanorhynchids (P. dipsacum, C. gracilis and N. bisulcata) in their muscles. Among fishes, both L. lentjan and T. tonggol were the most infected hosts, as each of them harbors three different trypanorhynchids.